Exploratory study of the characteristics of autonomous work in university students - Riveros Ferrada, Carolina; Loyola Carrillo, Paola (Revista Pedagogía Universitaria y Didáctica del Derecho, 2016)
Autonomous work of students is a fundamental aspect for the development of models based on competition. This paper is based on the responses to an autonomous work strategies questionnaire (CETA) applied to University of Talca law students. Results show that the students commonly develop strategies such as preparation for exams and conceptualization, while the least elaborated are planning and collaboration. Nevertheless, the averages are similar in every strategy, that is to say each one is moderately evolved. Therefore, these strategies must be perfected and strengthened to reach better results on skills development.